Exposure to crack cocaine causes adverse effects on marine mussels Perna perna. Issue 1 (15th October 2017) - Maranho, L.A.; Fontes, M.K.; Kamimura, A.S.S.; Nobre, C.R.; Moreno, B.B.; Pusceddu, F.H.; Cortez, F.S.; Lebre, D.T.; Marques, J.R.; Abessa, D.M.S.; Ribeiro, D.A.; Pereira, C.D.S.
Abstract: Our study aimed to evaluate crack cocaine effects in different life stages of the marine mussel Perna perna . For this purpose, fertilization rate, embryo-larval development, lysosomal membrane stability and DNA strand breaks were assessed. Effect concentrations in gametes and in larval development were found after 1 h (IC50  = 23.53 mg·L − 1 ) and 48 h (IC50  = 16.31 mg·L − 1 ), respectively. The highest tested concentration showing no acute toxicity (NOEC) was 10 mg·L − 1, while the lowest observed effect concentration (LOEC) was 20 mg·L − 1 . NOEC concerning embryo-larval development was 0.625 mg·L − 1, while the LOEC was 1.25 mg·L − 1 . Cyto-genotoxic effects were evidenced in mussels exposed to crack cocaine concentrations ranging from 5 to 500 μg·L − 1 . Our results report the first data on effects of an illicit drug to marine organisms and should encourage further ecotoxicological studies of these contaminants of emerging concern in coastal ecosystems. Highlights: First data on biological effects of an illicit drug to marine organism Toxicity to gametes and embryos exposed to crack cocaine Cyto-genotoxicity observed in adult mussels exposed for 48 h Adverse effects at environmentally relevant concentrations of cocaine